Antibacterial and anti-mineralization material for softening dental calculus and inhibiting formation of dental calculus

By combining chitosan and carboxymethyl chitosan with 1-hydroxybenzotriazole, organic additives and lysozyme to form a nanocomposite, the problems of poor biocompatibility and calculus residue in calculus softeners are solved, achieving long-term inhibition of calculus remineralization and tissue repair in periodontal pockets.

CN121668288APending Publication Date: 2026-03-17XIAN MANTES BIOTECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511796209.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-12-02
Publication Date
2026-03-17

AI Technical Summary

Technical Problem

Existing tartar softeners have poor biocompatibility and unsatisfactory tartar softening effects. Tartar residue in periodontal pockets leads to recurrent inflammation, and there is a lack of materials that can effectively inhibit tartar remineralization.

Method used

A nanocomposite is formed by combining chitosan and/or carboxymethyl chitosan with 1-hydroxybenzotriazole, organic additives and lysozyme through an amidation reaction. This nanocomposite has antibacterial and antimineralization effects and inhibits tartar formation.

Benefits of technology

It softens tartar before basic periodontal treatment, and inhibits tartar reformation after treatment by using an antibacterial and mineralization-blocking defense line, promoting periodontal tissue repair. It has good biocompatibility and low allergenicity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121668288A_ABST
    Figure CN121668288A_ABST
Patent Text Reader

Abstract

The invention provides an antibacterial and anti-mineralization material for softening dental calculus and inhibiting formation of dental calculus, a preparation method of the antibacterial and anti-mineralization material comprises the following steps: dissolving chitosan and / or carboxymethyl chitosan and 1-hydroxybenzotriazole in deionized water under a stirring condition to obtain a solution A; under the stirring condition, an organic additive solution and a 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride solution are dropwise added into the solution A obtained in the step 1), and a solution B is obtained; performing low-temperature dialysis on the solution B obtained in the step 2), and performing freeze drying to obtain a product C; under the stirring condition, adding the product C and lysozyme into deionized water, and reacting to obtain the antibacterial and anti-mineralization material for softening dental calculus and inhibiting formation of dental calculus. The material disclosed by the invention can be combined with the surface of residual dental calculus after periodontal basic treatment, surface plaque biofilm is removed, and rapid mineralization of the material is inhibited by combining calcium ions, cell colonization is promoted, and periodontal tissue recovery is promoted.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of biomaterials technology, and in particular relates to an antibacterial and antimineralization material that softens dental calculus and inhibits its formation. Background Technology

[0002] Currently, common tartar softeners mainly use EDTA (ethylenediaminetetraacetic acid) as the active ingredient. However, traditional tartar softeners have certain limitations, such as poor biocompatibility, unsatisfactory tartar softening effect, and single function, which limits their use.

[0003] On the other hand, in basic periodontal treatment, subgingival scaling and root planing are key steps in calculus removal, but their effectiveness is often limited by the anatomical morphology of the periodontal pocket and the range of instrument operation, leaving calculus residue in deep pocket areas. This residual calculus not only becomes a matrix for plaque biofilm reattachment but is also more prone to pathological remineralization, leading to recurrence of inflammation and further damage to periodontal supporting tissues. Currently, there is a lack of a long-lasting functional material that can remain within the periodontal pocket after treatment to block microbial biofilm regeneration and calcium salt deposition, thereby inhibiting rapid calculus remineralization. Summary of the Invention

[0004] In view of this, the present invention aims to provide an antibacterial and antimineralization material for softening tartar and inhibiting its formation, in order to overcome the shortcomings of the prior art. The present invention provides an antibacterial-antimineralization material for softening tartar before basic periodontal treatment and for blocking the rapid mineralization of tartar after basic periodontal treatment. It can soften the tartar structure before basic periodontal treatment, which is beneficial to subsequent basic periodontal treatment, and after basic treatment, it inhibits the formation of tartar through two lines of defense: antibacterial and antimineralization, and promotes cell colonization, which helps periodontal tissue repair.

[0005] To achieve the above objectives, the technical solution of the present invention is implemented as follows: An antibacterial and antimineralizing material for softening and inhibiting tartar formation is prepared by the following steps. 1) Under stirring conditions, chitosan and / or carboxymethyl chitosan and 1-hydroxybenzotriazole are dissolved in deionized water to obtain solution A; the mass ratio of 1-hydroxybenzotriazole to chitosan and / or carboxymethyl chitosan is 1:1 to 1:1.5. 2) Under stirring conditions, add organic additives and 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride solution to solution A from step 1) to obtain solution B; 3) Dialyze the solution B obtained in step 2) at low temperature and freeze-dry it to obtain product C; 4) Add product C and lysozyme to deionized water and stir to obtain an antibacterial and antimineralizing material that softens tartar and inhibits its formation.

[0006] Preferably, in step 1), the mass ratio of chitosan and / or carboxymethyl chitosan to deionized water is 1:50 to 1:100.

[0007] Preferably, in step 2), the organic additive is one or more of gallic acid, catechin gallic acid, phytic acid, citric acid, and tartaric acid.

[0008] Preferably, the mass ratio of chitosan and / or carboxymethyl chitosan to organic additives is 1:0.5 to 1:1; the mass ratio of organic additives to 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride is 1:1 to 1:2.

[0009] Preferably, in step 4), the mass ratio of product C to lysozyme is 1:(1~4), and the final concentration of lysozyme is 0.5~4mM; preferably, 1~2mM.

[0010] Preferably, the stirring speed in steps 1) and 2) is 300 r / min to 500 r / min, and the stirring time is 24 h to 48 h; the stirring speed in step 4) is 200 r / min to 400 r / min, and the stirring time is 4 h to 8 h.

[0011] Preferably, in step 3), the temperature of low-temperature dialysis is 2℃~6℃ and the time is 36h~48h; the temperature of freeze drying is -45℃~-30℃ and the time is 24h~72h, preferably 24h~48h.

[0012] Preferably, in step 3), the dialysate for low-temperature dialysis is deionized water; it is changed every 8 hours.

[0013] Preferably, step 1) further includes centrifuging solution A at 2000 rpm to 4000 rpm for 8 min to 15 min to remove impurities; steps 2) and 4) are carried out under light-protected conditions.

[0014] This invention also provides the application of the above-described antibacterial and antimineralizing materials for softening tartar and inhibiting tartar formation in the preparation of drugs or care products for periodontal basic treatment or periodontitis.

[0015] Subgingival calculus is difficult to completely remove during clinical procedures, and residual small calculus particles can become mineralization nuclei for bacterial adsorption and calculus re-formation. Therefore, inhibiting calculus formation after basic periodontal treatment is of significant clinical importance. The amino groups in chitosan and carboxymethyl chitosan can graft with the carboxyl groups in gallic acid, tartaric acid, and citric acid through amidation reactions under the action of cross-linking agents, forming polyelectrolyte complexes with phytate ions. Lysozyme can bind to the grafted products through intermolecular hydrogen bonds, forming nanocomplexes. Lysozyme and organic additives have good antibacterial effects; the phenolic hydroxyl groups of gallic acid can chelate calcium ions; citric acid and tartaric acid chelate calcium ions through their carboxyl groups; and citric acid chelates calcium ions through its phosphate groups. By reducing the number of free calcium ions, calculus mineralization is inhibited.

[0016] Compared with the prior art, the present invention has the following advantages: This invention relates to an antibacterial and antimineralizing material that softens dental calculus and inhibits its formation. It features a rational structural design and a simple preparation method. It can soften dental calculus before basic periodontal treatment to facilitate subsequent treatment, and after basic periodontal treatment, it effectively removes plaque biofilm through a dual defense of antibacterial and mineralization-blocking mechanisms, while inhibiting rapid calculus mineralization to promote periodontal tissue repair. It is non-toxic, non-irritating, has good biocompatibility and low allergenicity, and exhibits ideal therapeutic effects. Attached Figure Description

[0017] The accompanying drawings, which form part of this invention, are used to provide a further understanding of the invention. The illustrative embodiments of the invention and their descriptions are used to explain the invention and do not constitute an undue limitation on the invention. In the drawings: Figure 1 The image shows a transmission electron microscope (TEM) image of the nanocomposite prepared in Example 1.

[0018] Figure 2 The image shows a transmission electron microscope (TEM) image of the nanocomposite prepared in Example 1 that inhibits the rapid mineralization of hydroxyapatite. The results show that, under the action of the nanocomposite, percalcite and hydroxyapatite coexist in the mineralization solution (a); in the blank control group, only needle-like hydroxyapatite is present (b).

[0019] Figure 3 To evaluate the antibacterial properties of the nanocomposite prepared in Example 1, the number of dead bacteria with red fluorescence (a) was significantly increased in the nanocomposite group compared to the blank group (b).

[0020] Figure 4 This is a transmission electron microscope image of the nanocomposite prepared in Example 2.

[0021] Figure 5The image shows a transmission electron microscope (TEM) image of the nanocomposite prepared in Example 2 that inhibited the rapid mineralization of hydroxyapatite. The results show that under the action of the nanocomposite, percalcite and hydroxyapatite coexist in the mineralization solution and no dense mineralization layer is formed (a). A dense mineralization layer was formed in the blank control group (b).

[0022] Figure 6 To evaluate the antibacterial properties of the nanocomposite in Example 2, the number of dead bacteria with red fluorescence (a) was significantly increased in the nanocomposite group compared to the blank group (b).

[0023] Figure 7 The image shows a scanning electron microscope (SEM) image of the nanocomposite prepared in Example 3.

[0024] Figure 8 The images show scanning electron microscopy (SEM) images of the nanocomposite prepared in Example 3 softening dental calculus. The results show that under the action of the nanocomposite, a dense mineralization layer was not formed in the mineralization solution (a); a dense mineralization layer was formed in the blank control group (b).

[0025] Figure 9 The image shows a scanning electron microscope (SEM) image of the nanocomposite prepared in Example 4.

[0026] Figure 10 The image shows a scanning electron microscope image of the nanocomposite prepared in Example 4 softening dental calculus. The results show that no dense mineralization layer was formed in the mineralization solution under the action of the nanocomposite (a); in the blank control group, only needle-like hydroxyapatite was present (b). Detailed Implementation

[0027] Unless otherwise defined, the technical terms used in the following embodiments have the same meanings as commonly understood by those skilled in the art. Unless otherwise specified, the experimental reagents used in the following embodiments are conventional biochemical reagents; and the experimental methods described are conventional methods.

[0028] The present invention will be described in detail below with reference to the embodiments.

[0029] Example 1

[0030] An antibacterial and antimineralizing material that softens dental calculus and inhibits its formation is prepared through the following steps. 1) Under the condition of stirring speed of 300 rpm, dissolve 0.350 g of chitosan and 0.282 g of 1-hydroxybenzotriazole in 30 mL of deionized water and stir for 24 h to obtain solution A; centrifuge solution A at 3000 rpm for 10 min and take the supernatant to remove impurities.

[0031] 2) Under the condition of stirring speed of 300 rpm, add 0.311 g of gallic acid powder to solution A after removing impurities, and add 2 mL of anhydrous ethanol solution containing 0.355 g EDC·HCl dropwise. React in the dark for 24 h to obtain solution B.

[0032] 3) Dialyze the solution B obtained in step 2) at 4℃ for 48 h using a dialysis bag (MWCO 8-14 kDa) (change the solution every 8 h), centrifuge at 3000 rpm for 10 min, collect the supernatant, and freeze-dry at -40℃ for 24 h to obtain product C.

[0033] 4) Dissolve 0.3 g of product C in 30 mL of deionized water to obtain solution D; slowly add 5 mL of deionized water containing 0.5 g of lysozyme to solution D, react at 300 rpm for 4 h to obtain nanocomposite solution, which is an antibacterial and antimineralization material solution for softening tartar and inhibiting tartar formation.

[0034] Example 2

[0035] An antibacterial and antimineralizing material that softens dental calculus and inhibits its formation is prepared through the following steps. 1) Under the condition of stirring speed of 300 rpm, 0.350 g of chitosan and 0.282 g of 1-hydroxybenzotriazole were dissolved in 30 mL of deionized water and stirred for 24 h to obtain solution A; solution A was centrifuged at 3000 rpm for 10 min to remove the supernatant and impurities.

[0036] 2) Under the condition of stirring speed of 300 rpm, add 5 mL of solution containing 0.28 g of citric acid to solution A after removing impurities, and add 2 mL of anhydrous ethanol solution containing 0.355 g EDC·HCl dropwise. React in the dark for 24 h to obtain solution B.

[0037] 3) Dialyze the solution B obtained in step 2) at 4℃ for 48 h using a dialysis bag (MWCO 8-14 kDa) (change the solution every 8 h), centrifuge at 3000 rpm for 10 min, collect the supernatant, and freeze-dry at -40℃ for 24 h to obtain product C.

[0038] 4) Dissolve 0.3 g of product C in 30 mL of deionized water to obtain solution D; slowly add 5 mL of deionized water containing 0.5 g of lysozyme to solution D, react at 300 rpm for 4 h to obtain nanocomposite solution, which is an antibacterial and antimineralization material solution for softening dental calculus and inhibiting its formation.

[0039] Example 3

[0040] An antibacterial and antimineralizing material that softens dental calculus and inhibits its formation is prepared through the following steps. 1) Under the condition of stirring speed of 300 rpm, 0.32 g of carboxymethyl chitosan and 0.282 g of 1-hydroxybenzotriazole were dissolved in 30 mL of deionized water and stirred for 24 h to obtain solution A; solution A was centrifuged at 3000 rpm for 10 min to remove the supernatant and impurities.

[0041] 2) Under the condition of stirring speed of 300 rpm, add 0.311 g of gallic acid powder to solution A after removing impurities, and add 2 mL of anhydrous ethanol solution containing 0.355 g EDC·HCl dropwise. React in the dark for 24 h to obtain solution B.

[0042] 3) Dialyze the solution B obtained in step 2) at 4℃ for 48 h using a dialysis bag (MWCO 8-14 kDa) (change the solution every 8 h), centrifuge at 3000 rpm for 10 min, collect the supernatant, and freeze-dry at -40℃ for 24 h to obtain product C.

[0043] 4) Dissolve 0.3 g of product C in 30 mL of deionized water to obtain solution D; slowly add 5 mL of deionized water containing 0.5 g of lysozyme to solution D, react at 300 rpm for 4 h to obtain nanocomposite solution, which is an antibacterial and antimineralization material solution for softening dental calculus and inhibiting its formation.

[0044] Example 4

[0045] An antibacterial and antimineralizing material that softens dental calculus and inhibits its formation is prepared through the following steps. 1) Under the condition of stirring speed of 300 rpm, 0.32 g of carboxymethyl chitosan and 0.282 g of 1-hydroxybenzotriazole were dissolved in 30 mL of deionized water and stirred for 24 h to obtain solution A; solution A was centrifuged at 3000 rpm for 10 min to remove the supernatant and impurities.

[0046] 2) Under the condition of stirring speed of 300 rpm, add 5 mL of solution containing 0.28 g of citric acid to solution A after removing impurities, and add 2 mL of anhydrous ethanol solution containing 0.355 g EDC·HCl dropwise. React in the dark for 24 h to obtain solution B.

[0047] 3) Dialyze the solution B obtained in step 2) at 4℃ for 48 h using a dialysis bag (MWCO 8-14 kDa) (change the solution every 8 h), centrifuge at 3000 rpm for 10 min, collect the supernatant, and freeze-dry at -40℃ for 24 h to obtain product C.

[0048] 4) Dissolve 0.3 g of product C in 30 mL of deionized water to obtain solution D; slowly add 5 mL of deionized water containing 0.5 g of lysozyme to solution D, react at 300 rpm for 4 h to obtain nanocomposite solution, which is an antibacterial and antimineralization material solution for softening tartar and inhibiting tartar formation.

[0049] In Examples 1 to 4, steps 2) and 4) are performed under light-protected conditions.

[0050] Experiment 1 The nanocomposite solutions from steps 4) of Example 1 and 4) of Example 2 were dropped onto a copper grid and then detected by TEM. The results are shown in [Figure 1]. Figure 1 , Figure 4 The nanocomposite solutions from steps 4) of Example 3 and 4) were dropped onto a silicon wafer, dried, sputter-coated with gold, and then used for SEM detection. The results are shown in [Figure 4]. Figure 7 , Figure 9 .

[0051] Experiment 2 A solution of 0.1M calcium chloride and 0.06M ammonium dihydrogen phosphate (1:1, v / v, 20 mL) was prepared. A blank group (deionized water) and experimental groups (1 mg / mL, 10 mL) of the nanocomposite from steps 4 of Example 1 and 4 of Example 2 were used. The pH was adjusted to 7.0, and the mixture was stirred at 300 rpm for 2 h to obtain a solution. A drop of the solution was placed on a copper grid, allowed to air dry, and then used for TEM observation of its morphology. See [link to TEM]. Figure 2 , Figure 5 .

[0052] Experiment 3 A hydroxyapatite solution was obtained by adjusting the pH to 9.0 with a 1:1 (v / v) solution of 0.1M calcium chloride and 0.06M ammonium dihydrogen phosphate (20 mL) and stirring at 300 rpm for 2 h. A blank group was set up using deionized water, and the experimental group consisted of the nanocomposite (1 mg / mL, 10 mL) from steps 4 of Example 3 and 4 of Example 4. 10 mL of the nanocomposite solution was added to 10 mL of the hydroxyapatite solution, and the reaction was carried out at 300 rpm for 1 h. The resulting solution was centrifuged at 3000 rpm for 10 min, the precipitate was collected, and freeze-dried to obtain the product. The product was picked up with a toothpick, and a small amount was spread onto conductive adhesive by rolling the toothpick. Unattached powder was blown away in one direction with an air gun to ensure uniform sample distribution. After gold sputtering on the sample stage, the sample was observed using SEM. Figure 8 , Figure 10 .

[0053] Experiment 4 Porphyromonas gingivalis and Fusobacterium nucleatum (1×10⁻⁶) were cultured in 1 mL of BHI broth. 8CFU / mL bacterial suspensions were cultured in 35 mm laser confocal microplates. *Porphyromonas gingivalis* and *Fusobacterium nucleatum* were cultured for 96 h and 72 h, respectively, to form biofilms at the bottom of the plates. The BHI broth medium was replaced every 48 h. After biofilm formation, 500 μL of PBS solution was added to the blank group, and 500 μL of the nanocomposite (500 μg / mL) from steps 4) of Example 1 and 4) of Example 2 was added to the experimental group. After culturing for another day, the biofilms were stained using a live / dead bacteria staining kit. After staining for 30 min, the biofilms were observed under light using a laser confocal microscope to obtain fluorescence images. See [link to relevant documentation]. Figure 3 , Figure 6 .

[0054] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. An antibacterial antiminerai material for softening dental calculus and inhibiting dental stone formation, characterized by comprising: The preparation method comprises the following steps, ​ 1) dissolving chitosan and / or carboxymethyl chitosan and 1-hydroxybenzotriazole in deionized water under stirring to obtain solution A; the mass ratio of 1-hydroxybenzotriazole to chitosan and / or carboxymethyl chitosan is 1:1~1:1.5; 2) adding an organic additive and 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride solution to the solution A of step 1) under stirring to obtain solution B; 3) low-temperature dialysis of the solution B obtained in step 2), freeze-drying to obtain product C; 4) adding product C and lysozyme to deionized water and stirring to obtain an antibacterial and anti-mineralization material for softening dental calculus and inhibiting calculus formation.

2. The antibacterial anti-mineralization material for softening dental calculus and inhibiting dental stone formation according to claim 1, characterized by: In step 1), the mass ratio of chitosan and / or carboxymethyl chitosan to deionized water is 1:50~1:

100.

3. The antibacterial anti-mineralization material for softening dental calculus and inhibiting dental stone formation according to claim 1, wherein: In step 2), the organic additive is one or two or more of gallic acid, catechin gallate, phytic acid, citric acid and tartaric acid.

4. The antibacterial anti-mineralization material for softening dental calculus and inhibiting dental stone formation according to claim 1, wherein: The mass ratio of chitosan and / or carboxymethyl chitosan to the organic additive is 1:0.5~1:1; the mass ratio of the organic additive to 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride is 1:1~1:

2.

5. The antibacterial anti-mineralization material for softening dental calculus and inhibiting dental stone formation according to claim 1, wherein: In step 4), the mass ratio of product C to lysozyme is 1:(1~4), and the final concentration of lysozyme is 0.5~4mM.

6. The antibacterial anti-mineralization material for softening dental calculus and inhibiting dental stone formation according to claim 1, wherein: The stirring speed in steps 1) and 2) is 300r / min~500r / min, and the stirring time is 24h~48h; the stirring speed in step 4) is 200r / min~400r / min, and the stirring time is 4h~8h.

7. The antibacterial anti-mineralization material for softening dental calculus and inhibiting dental stone formation according to claim 1, wherein: In step 3), the temperature for low-temperature dialysis is 2℃~6℃, and the time is 36h~48h; the temperature for freeze-drying is -45℃~-30℃, and the time is 24h~72h.

8. The antibacterial anti-mineralization material for softening dental calculus and inhibiting dental stone formation according to claim 1, wherein: In step 3), the dialysis solution for low-temperature dialysis is deionized water; the dialysis solution is replaced every 8h.

9. The antibacterial anti-mineralization material for softening dental calculus and inhibiting dental stone formation according to claim 1, wherein: In step 1), solution A is further centrifuged at 2000rpm~4000rpm for 8min~15min to remove impurities; steps 2) and 4) are carried out in the dark.

10. Use of the antibacterial and anti-mineralization material for softening dental calculus and inhibiting calculus formation according to any one of claims 1~9 in the preparation of a drug or care product for periodontal basic treatment or periodontitis.

Citation Information

Patent Citations

  • Polyethyleneimine mouthwash capable of preventing dental plaque and dental calculus and preparation method thereof

    CN108451792A

  • Water-soluble chitosan antimicrobial derivative and preparation method therefor

    WO2019052321A1